Exploring barriers and enablers to the delivery of Making Every Contact Count brief behavioural interventions in Ireland: a cross-sectional survey study - Hayes, Catherine (My University, 2023)
Objectives The public health impact of the Irish Making Every Contact Count (MECC) brief intervention programme is dependent on delivery by health care professionals. We aimed to identify enablers and modifiable barriers to MECC intervention delivery to optimize MECC implementation. Design Online cross-sectional survey design. Methods Health care professionals (n = 4050) who completed MECC eLearning were invited to complete an online survey based on the Theoretical Domains Framework (TDF). Multiple regression analysis identified predictors of MECC delivery (logistic regression to predict delivery or not; linear regression to predict frequency of delivery). Data were visualized using Confidence Interval-Based Estimates of Relevance (CIBER). Results Seventy-nine per cent of participants (n = 283/357) had delivered a MECC intervention. In the multiple logistic regression (Nagelkerke's R2 = .34), the significant enablers of intervention delivery were ‘professional role’ (OR = 1.86 [1.10, 3.15]) and ‘intentions/goals’ (OR = 4.75 [1.97, 11.45]); significant barriers included ‘optimistic beliefs about consequences’ (OR = .41 [.18, .94]) and ‘negative emotions’ (OR = .50 [.32, .77]). In the multiple linear regression (R2 = .29), the significant enablers of frequency of MECC delivery were ‘intentions/goals’ (b = 10.16, p = .02) and professional role (b = 6.72, p = .03); the significant barriers were ‘negative emotions’ (b = −4.74, p = .04) and ‘barriers to prioritisation’ (b = −5.00, p = .01). CIBER analyses suggested six predictive domains with substantial room for improvement: ‘intentions and goals’, ‘barriers to prioritisation’, ‘environmental resources’, ‘beliefs about capabilities’, ‘negative emotions’ and ‘skills’. Conclusion Implementation interventions to enhance MECC delivery should target intentions and goals, beliefs about capabilities, negative emotions, environmental resources, skills and barriers to prioritization.
PUBLISHED
Keywords: Alcohol and drug use; Behavioural intervention; Chronic illness prevention; eLearning; Smoking; Inclusive Society; Making Ireland; Primary care; Public health